Surgical Management of Acute Type A Aortic Dissection: An Overview. Issue 1 (March 2021) - Nagaradona, Sreedhar Reddy; Machiraju, Krishna; Kurapati, Srinivasulu Reddy; Boggula, Srinivas; Setty, Sridhar Anumala; Azam, Sadiq
Acute type A aortic dissection is a catastrophic disease that develops from a tear within the intima of the aortic wall, thereby creating a false lumen in the ascending aorta. Early suspicion, diagnosis, and prompt surgery play a key role in the survival of patients. It is a surgical emergency and requires replacement of the ascending aorta/aortic root with or without aortic arch replacement. Over the past decade the surgical outcomes have improved in specialized tertiary centers.